Comparison of Selected Anatomical and Treatment-related Diagnostic Parameters Estimated by Cone-Beam Computed Tomography and Digital Periapical Radiography in Teeth with Apical Periodontitis - Jelena Gudac; Kristina Hellén-Halme; Tadas Venskutonis; Algirdas Puisys; Vita Machiulskiene (eJournal of Oral Maxillofacial Research)
Objectives: To compare selected anatomical and treatment-related diagnostic parameters estimated by cone-beam computed tomography and by digital periapical radiography in teeth with apical periodontitis, and to evaluate reliability of different examiners in interpretation of images obtained by both methods.